Effect of Low Temperature Storage on Steroid Hormones Content Stability in Human Oocyte Follicular Fluid - Yakovleva, E. A.; Gerodes, A. G. (Problems of Cryobiology and Cryomedicine, 2004)
There was studied the estradiol (E), progesterone (P) and testosterone (T) content in follicular fluid (FF) of human oocyte preovulatory follicles, native and low-temperature-stored one (-196Â°C). We have compared the effect of two freezing regimens (one-step immersion into liquid nitrogen and a two-step one with the preliminary exposure in nitrogen vapors) on the stability of concentration maintenance of these hormones in FF for 1 and 6 months. Stability of estradiol, progesterone and testosterone was shown to be kept within the whole observation period and to be independent upon the FL freezing regimen selected.